Novel Variation in Acyl-CoA Synthetase Long Chain Family Member 6 (ACSL6) Results in Protein Structural Modification and Multiple Non-Related Neoplasia in a 46-Year-Old: Case Report - Castillo, María Isabel; Freire, Erick; Romero, Vanessa I.; Arias-Almeida, Benjamín; Reyes, Carlos; Hosomichi, Kazuyoshi (Frontiers in Oncology, 2022)
Multiple non-related neoplasia does not have an established approach or benefits for performing whole-exome sequencing (WES) analysis. We report on a 46-year-old woman who developed astrocytoma, thyroid, and breast cancer within 10 years. The WES analysis found a novel missense variant in the ACSL6 gene, and the protein modeling showed altered secondary and tertiary structures, which modify the binding to cofactors and substrates. ACSL6 is involved in lipid metabolism, expressed in the brain, thyroid, and breast tissues, and is associated with diverse types of cancer. Our study demonstrates the benefit of WES analysis compared with commercial panels in patients with non-related neoplasia.